pengaruh film animasi nussa dan rara untuk meningkatkan nilai agama dan moral anak usia 5-6 tahun di tk pembina kaur selatan kabupaten kaur - Novi, Novi Novi; Nirwana, Evi Selva (Peneliti.net, 2026)
This study aims to determine the effect of the Nussa and Rara animated film to improve the religious and moral values of 5-6 year old children at the South Kaur Pembina Kindergarten, Kaur Regency. Children aged 5-6 years in this institution still need stimulation to improve their religious and moral values. This study uses a quantitative experimental method approach. Data were collected through observation and documentation of teachers and early childhood as the main subjects. The results of the study indicate that the Nussa and Rara animated film is used by teachers to improve the religious and moral values of early childhood. Although there are obstacles such as differences in children's understanding and advertising interruptions while watching. The Nussa and Rara animated film is proven to be effective in improving the religious and moral values of children aged 5-6 years.